PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, KOMPETENSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI KSP SUMBER JAYA LAMONGAN - Miftahul Huda; Moh. Azus Shony Azar (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2020)
The research is determine the effect of leadership, organizational culture, competence and motivation on employee performance at KSP Sumber Jaya Lamongan. The population in this study are employees at KSP Sumber Jaya Lamongan while the sample population were all employees of cooperatives totaling 30 people, sampling techniques is the saturation sampling because the entire population is used as a sample and also less than 30 people.To obtain the necessary data the authors used data collection techniques such as interviews and questionnaires, techniqueanalysis used in this research is descriptive method. From the discussion concluded that KSP Sumber Jaya Lamongan is a savings and credit cooperatives in which variable competence and work motivation are effected significsnt partially on the performance of employees in KSP Sumber Jaya Lamongan while the leadership and organizational culture are not effected significant partially on performance employeer of at KSP Sumber Jaya Lamongan. So the contribution of variable influence leadership competencies organizational culture and work motivation on employee performance in KSP Sumber Jaya Lamongan amounted to 78.4%, while the remaining 21.6% is influenced by other variables that not examined.